SUSTAINABLE URBAN FARMING THROUGH HOUSEHOLD WASTE UTILIZATION: A COMMUNITY ENGAGEMENT INITIATIVE IN PKK RW IX GRIYA BHAYANGKARA, SIDOARJO - Ramadhani Mahendra Kusuma; Fitri Wijayanti; Puji Lestari Tarigan; Purnomo Edi Sasongko; Yudi Nur Supriadi (LPPM Universitas Bina Bangsa, 2023)
This community engagement initiative focused on promoting sustainable urban farming practices in Balai RW IX Griya Bhayangkara, Sidoarjo, East Java. The program, carried out in collaboration with academic teams from Universitas Pembangunan Nasional